Dermatological changes in pregnant women treated in public health units - Magalhães, Michelle; Ferreira, Antonio Bruno C.; Zamberlan, Claudia; Bianchini, Leonardo O. F.; Monçalves, Kelvin Leandro M.; Júnior, Luiz Fernando Rodrigues; Benedetti, Franceliane Jobim (International Journal of Research in Dermatology, 2025)
Background: Pregnancy, particularly its second and third trimesters, causes intense physical, emotional, and psychological changes in women, including the skin, hair, and nails. Objectives were to describe the association between dermatological changes and sociodemographic conditions, anthropometric nutritional status, and previous and gestational diseases. Methods: This cross-sectional study was conducted in Brazilian public health units, including women in the third trimester of pregnancy with or without dermatological lesions. They answered a questionnaire with sociodemographic data, health history, and dermatological changes. The researchers photographed the lesions and recorded the dermatological and anthropometric assessment results on a form. They used statistical tests (e.g., ANOVA and chi-square) and Spearman’s correlation, with a 5% significance level. Results: The study analyzed 100 pregnant women with a mean age of 26.35±6.49 years and a mean income of 1.68±0.72 Brazilian minimum wages; 30 (30%) women had previous diseases, and 64 (64%) did not report obstetric history. Phototype II was the most common, in 41 (41%) women, and hyperchromia and stretch marks were the most frequent dermatoses. Pre-gestational BMI correlated significantly with the number of dermatological changes-which had a higher prevalence in obese pregnant women. Thin pregnant women had a mean of 2.75±0.95a dermatological changes; normal-weight women, 2.50±1.34ab; overweight, 3.16±1.34a; and obese, 3.55±1.21ac (p=0.014). Furthermore, 82.8% of patients with stretch marks had inadequate weight gain. Conclusions: The study highlights the complexity of obstetric care in this population, requiring a multidisciplinary approach in prenatal care, focusing on managing metabolic and cardiovascular comorbidities, weight control, and prevention of dermatological complications.